On the luminescence signals of empty sample carriers - Schmidt, Christoph; Kreutzer, Sebastian; Fattahi, Morteza; Bailey, Richard; Zander, Anja; Zöller, Ludwig (Ancient TL, 2011)
Luminescence dating is a leading technique for a large spectrum of Quaternary dating applications. Since the development of automated reader systems, handling great amounts of samples has become possible. A large quantity of data is produced in a short time and a detailed check of every single curve is often impractical. Therefore, it is important to be confident in excluding any kind of unwanted signal contributions, such as those from sample carriers. For commonly used types of steel and aluminium (Al) carriers from three laboratories, luminescence characteristics of spurious and radiation-induced signals are presented. TL and OSL emissions of discs show natural (Al) and regenerated thermally stable signals in the UV, UV-blue and red detection range. These signals have characteristic saturation doses of several hundred Gy. Furthermore, we demonstrate light insensitive signal components and phototransferred thermoluminescence (PTTL). Due to high scatter between discs, the proportion of unwanted disc signal contribution to the entire signal is difficult to predict, without direct measurement. The sources of these signals are possibly chemical compounds acting as luminophores or oxide layers (Al2O3 layers in case of Al discs).
Gesehen am 31-03-2025